The Regulation of Integrity Zone and the Corruption-Free Zone in Indonesia and Rusia - Widyawati, Anis; Latifiani, Dian; Arifin, Ridwan; Ompoy, Genjie; Zaki, Nurul Natasha Binti Muhammad (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2023)
This research aims to identify and analyze the integrity zone as an innovative strategy to combat corruption. The research methodology uses normative juridical analysis, which is legal research that examines law from an internal perspective, with the object of its study being the legal norm, which involves literature analysis, qualitative approach, and comparative approach on the implementation of the integrity zone and the administrative law policy through the Corruption-Free Zone (WBK) in Indonesian governmental institutions. The results of the study indicate that the integrity zone approach involves mapping corruption-prone areas and proactively implementing preventive measures in these zones. This strategy includes increasing awareness, enforcing regulations, and strengthening supervision. Furthermore, this paper also discusses the challenges and opportunities in implementing the integrity zone and the WBK in Indonesia, along with providing policy recommendations to maximize the effectiveness of this approach in minimizing corruption and enhancing integrity within the scope of the Indonesian government administration. Implementing the integrity zone concept is expected to bring about positive changes in the efforts to eradicate corruption and build more transparent and integrity-driven governance in Indonesia.